THE INFLUENCE OF FIRM SIZE AND GEARING ON INCREASE IN PROFITS IN CUISINE AND REFRESHMENT SUB-SEGMENT ORGANIZATIONS REGISTERED ON THE INDONESIA EQUITY MARKET FOR THE PERIOD 2018-2022 - Fajaryati, Hijroini; Sunarti, Desi; Nurhasanah, Nurhasanah; Ayudia, Rosalina; Suripto, Suripto (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
The objective of this research is to analyze whether there is an impact of company size and gearing on profit growth in the culinary and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. In this study, the dependent variable is profit growth, while the independent variables are company size and gearing. This study uses a quantitative analysis method and purposive sampling technique, utilizing annual financial report data from sixteen culinary and beverage sub-sector companies listed on the IDX. Data testing in this research was conducted using SPSS software version 26. After testing, both variables were found to be valid and reliable. According to this research, the company size variable does not have a significant positive impact on profit growth in culinary and beverage sub-sector companies listed on the IDX. The second finding of this research indicates that the gearing variable has a significant negative impact on profit growth, suggesting that companies with a high debt-to-equity ratio experience an increase in debt usage as a source of funding, which burdens the company with high interest expenses that must be paid, ultimately leading to a decrease in company profits.